BIOMIMETIC NANOCOMPOSITE STRUCTURES DESIGNED FOR COATING OF ORTHOPEDIC IMPLANTS: AFM INVESTIGATION - BALINT, Reka; PETEAN, Ioan; FRANGOPOL, †Petre T.; MOCANU, Aurora; ARGHIR, George; RIGA, Sorin; TOMOAIA, Gheorghe; HOROVITZ, Ossi; TOMOAIA-COTISEL, Maria (Studia Universitatis Babeș-Bolyai Chemia, 2021)
Titanium implants are highly resistant to external forces and have affordable prices but the contact between Ti metal and surrounding native tissue could provoke an immunological response. The developing of biomimetic coating onto the Ti surface proves to be a smart choice to enhance the osseointegration and ensure an optimal healing process, due to the creation of nanostructured biomaterials like those in native bone. Thus, we designed a composite coating based on multi-substituted hydroxyapatite (noted ms-HAP or HAPc) nanoparticles, NPs, doped with essential elements: Mg, Zn and Si, functionalized with collagen type 1 (COL), embedded into poly lactic acid, PLA, matrix, and finally covered with COL layer to achieve biomimetic structures. Thin layers of biomimetic composite were self-assembled onto Ti surface via dip-coating method. Both, initial and coated Ti implants were investigated by atomic force microscopy (AFM), which allows surface investigation at high resolution of nano-level. COL amount in composite might self-assemble as COL fibers assuring a biomimetic structure, characterized by important features, like suitable porosity to facilitate the delivery of nutrients to osteoblasts and proper nano-topography and surface roughness to promote cell adhesion and proliferation. The outermost layer is of pure collagen which could assure a natural attachment to the bone tissue promoting osseo-integration.